2008
DOI: 10.1007/s11746-008-1315-x
|View full text |Cite
|
Sign up to set email alerts
|

Frying Stability of Canola Oil Blended with Palm Olein, Olive, and Corn Oils

Abstract: The fatty acid composition, peroxide value (PV), acid value (AV), iodine value (IV), total tocopherols (TT) content, and total phenolics (TP) content of canola oil (CAO), palm olein oil (POO), olive oil (OLO), corn oil (COO), and the binary and ternary blends of the CAO with the POO, OLO, and COO were determined. The blends were prepared in the volume ratios of 75:25 (CAO/POO, CAO/OLO, CAO/COO) and 75:15:10 (CAO/POO/OLO, CAO/POO/COO). The CAO and its blends were used to fry potato pieces (7.0 9 0.5 9 0.3 cm) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 19 publications
11
65
0
Order By: Relevance
“…Such results confirm good quality of refined rapeseed oil as frying medium in comparison with professional blend dedicated for frying. Obtained results are in agreement with other study with rapeseed oil used as a frying medium (Farhoosh et al 2008). Aladedunye and Przybylski (2009) observed that the contribution of total polar material increased consistently with frying time, achieving values of about 10 % for 7 h of deep frying.…”
Section: Discussionsupporting
confidence: 92%
“…Such results confirm good quality of refined rapeseed oil as frying medium in comparison with professional blend dedicated for frying. Obtained results are in agreement with other study with rapeseed oil used as a frying medium (Farhoosh et al 2008). Aladedunye and Przybylski (2009) observed that the contribution of total polar material increased consistently with frying time, achieving values of about 10 % for 7 h of deep frying.…”
Section: Discussionsupporting
confidence: 92%
“…The change in absorbance at 515 nm presents a measure of the scavenging effect of a particular extract for DPPH radicals. [22] The absorbance at 515 nm decreases as the reaction between antioxidant molecules and DPPH radicals progresses. Therefore, more potent antioxidant activity indicates a rapid decrease in the absorbance of the extract.…”
Section: Resultsmentioning
confidence: 99%
“…In our systematic review, we could not establish whether deep-fried potatoes were manufactured using sophisticated methods that can minimize these unwanted side effects, e.g. coating technologies, vacuum frying, or application of MUFA-rich oils to reduce trans fats [65,66].…”
Section: Discussionmentioning
confidence: 99%